Transmedia MOOC-ing: Breaking with tradition, for-credit MOOC design - Tombleson, Bridget; de Bussy, Nigel; Dobozy, Eva; Wolf, Katharina (2017)
This paper explores the use of transmedia pedagogy in a massive open online course (MOOC) environment for work integrated learning (WIL). Using a communication course as a case study, the paper seeks to understand how the use of transmedia pedagogy and a MOOC environment may create a democratic space for discovery learning and how it can improve connectedness between students, their peers and their supervisors (university and workplace). This conceptual paper forms the foundation of a longitudinal research project that seeks to understand to what extent transmedia pedagogy can enhance student connectedness and learning outcomes in a work integrated learning (WIL) MOOC environment. Transmedia pedagogy is relatively new and has been noted to create memorable learning through its narrative focus (Raybourn, 2014). Students have an opportunity to become active participants in their learning, and part of the educational environment that sees curriculum content created, shared and re-purposed by students as well as their educators. A MOOC environment, together with transmedia pedagogy may be able to bridge the gap of the connection between students and their resources, their educators and their peers. In theory, the transmedia pedagogy MOOC environment may provide opportunities for the creation of a holistic, democratic learning experience, which becomes particularly important for WIL courses where students do not attend classes. The MOOC re-imagined as a community encourages dialogue, interaction and the meeting of the personal and social aspects of learning (Kop, 2011). This synergetic relationship between a MOOC environment and transmedia pedagogy may be seen as “the scalable system of messages that unfolds from the use of multiple media, emotionally engaging learning by involving them personally in the story” (Raybourn, 2014, p. 472). Using a transmedia approach fosters both a participatory culture, where students see themselves as actively contributing to the curriculum content, and also peer collaboration, as they become part of an active online community of learners (Burdick & Willis, 2011). This study redefines the conceptualisation of MOOCs beyond the purpose of what they were designed and sees a new life-cycle introduced that re-purposes MOOCs to develop an online community of learners and further embed a reflective and immersive experience of learning. The paper seeks to fill a knowledge gap on the practical application of transmedia pedagogy in higher education and repurposing of MOOCs. Laurillard (2009) asks the question “how do we ensure that pedagogy exploits the technology, and not vice versa?” (p.6) and this paper will seek to determine how higher education can harness the democratic nature of the MOOC environment, for enrolled campus courses.